Cultivating Resilience: Climate-Smart Grass pea as a Multifunctional Feed, Forage, and Fodder Crop in Dry Areas through Integrated Genomic Approaches - Hassan, Sawsan; Louhaichi, Mounir; Agrawal, Shiv Kumar (International Livestock Research Institute, 2023)
The poster on "Cultivating Resilience: Climate-Smart Grass Pea as a Multifunctional Crop" underscores the potential of grass pea as a climate-smart resource for food, feed, and fodder. Highlighting high-yielding low-ODAP cultivars, the crop excels in fragile agro-ecosystems prone to drought, heat, and salinity. The context emphasizes climate-induced challenges, malnutrition, and the nutritional potential of grass pea, with the caveat of managing ODAP for safety. The innovative approach involves trait discovery, genebank material assessment, molecular breeding, and harnessing crop wild relatives. Progress includes expanding grass pea cultivation, relay planting in rice fields, and establishing global partnerships. Future steps involve Genome-wide Association Studies (GWAS) and genome editing for zero ODAP germplasm development.